Structural and Photoelectrochemical Properties of Cu-Doped CdS Thin Films Prepared by Ultrasonic Spray Pyrolysis. (25th February 2013) - Xie, Rui; Su, Jinzhan; Li, Mingtao; Guo, Liejin
Abstract : Cu-doped CdS thin films of variable doping levels have been deposited on indium tin oxide-coated glass substrate by simple and cost-effective ultrasonic spray pyrolysis. The influences of doping concentration and annealing treatment on the structure and photoelectrochemical properties of the films were investigated. The deposited films were characterized by XRD, SEM, and UV-Vis spectra. Moreover, the films were investigated by electrochemical and photoelectrochemical measurements with regard to splitting water for solar energy conversion. The results showed that the Cu impurity can cause a structural change and red shift of absorption edge. It was found that the photocurrent can be improved by the Cu-doping process for the unannealed films under the weak illumination. The unannealed 5 at.% Cu-doped sample obtained the maximum IPCE, which achieved about 45% at 0.3 V versus SCE potential under 420 nm wavelength photoirradiation. In addition, the p-type CdS was formed with a doping of 4 at.% 10 at.% Cu after 450°C 2 h annealed in vacuum.